ANALISIS PEMANFAATAN MEDIA DIGITAL DALAM MENGEMBANGKAN PROFIL PELAJAR PANCASILA PADA PEMBELAJARAN MATEMATIKA DI SDN TEGALGANDU 02 - Dwi Lia Sephiana; Muamar; Diah Sunarsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to describe the implementation of digital media and its impact in developing the profile of Pancasila students in mathematics learning at SDN Tegalgandu 02. This research method uses qualitative methods, using primary and secondary data. The researcher focuses on analyzing the use of digital media in mathematics learning at State Elementary Schools. Tegalgandu only focuses on analyzing the use of digital media. Data collection techniques using observation, interviews and documentation. Research results Implementation of digital media in developing Pancasila student profiles in mathematics learning as a new approach in education that gives schools the freedom to organize the Independent Curriculum involves the stages of planning, implementation and assessment. In the implementation stage, the teacher makes a learning video using the YouTube application which is adapted to the PPT taken from the LKS book for learning purposes. The implementation stage involves using learning methods that are appropriate to students' abilities and using PPT for learning. The impact of implementing digital media in developing student profiles of Pancasila in mathematics learning. Implementation of digital media in mathematics learning can have a positive impact on developing student profiles in understanding Pancasila values. Digital media can be used to convey mathematics material with an approach that strengthens Pancasila values ​​such as mutual cooperation, honesty and equality. For example, using online learning platforms that encourage collaboration between students to solve math problems can build a spirit of mutual cooperation. In addition, through digital media, learning can be tailored to students' individual needs and abilities.